Dorta Jagić — poetka wolności. Komentarz do Bibliografii przekładów literatury chorwackiej w Polsce w 2014 roku - Majdzik, Katarzyna (Przekłady Literatur Słowiańskich, 2015)
Dorta Jagić — the poetess of freedom. The commentary to the Bibliography of the translations of Croatian literature in Poland in 2014 The year 2014 in Poland did not teem with many publications of Croatian literary works. In journals of culture and literature there were published a dozen or so poems and prose excerpts, less essays and plays. Among book publications attention should be paid to the collection of essays by Dubravka Ugresić Karaoke culture, the selection of poems by Ivan Herceg and the poetic tome by Dorta Jagić Sofa on the market. The last mentioned was awarded during the prestigious literary contest „The European Poet of Freedom” taking place in Gdańsk. Apart from the poetess the jury set the translator Małgorzata Wierzbicka apart for distinction. The article discusses selected poems by Dorta Jagić from the awarded collection. Key words: Croatian literature, translations, Dorta Jagić, The European Poet of Freedom, bibliography